Numerical investigation of flow features in the vaneless region of a centrifugal pump by large eddy simulation. Issue 1 (5th March 2018) - Huang, Xianbei; Li, Yaojun; Liu, Zhuqing; Yang, Wei
Abstract : Purpose: The purpose of this paper is to obtain a better understanding of the rotor–stator interaction in the vaneless region of a centrifugal pump. Design/methodology/approach: A third-order sub-grid scale (SGS) model containing the rotation rate tensor named the dynamic cubic non-linear model (DCNM) is used for simulating the flow field in a centrifugal pump with a vaned diffuser. The pressure coefficient and velocity distributions are compared with the experimental data. Focusing on the vaneless region, the pressure pulsation, Reynolds stress pulsation and Reynolds stress transport equation are analyzed. Findings: The comparison of the calculation results with the experimental data indicates that the DCNM can accurately capture the distributions of pressure and velocity in the vaneless region. Based on the instantaneous pressure signals, the pressure pulsation is analyzed to show that in the vaneless region, the dominant frequency near the impeller is twice the blade passing frequency, whereas it is equal to the blade passing frequency near the diffuser. Further exploration of the Reynolds stress pulsation shows the correlation between the two variables. Additionally, the extreme low frequency of Reynolds stress near the diffuser is found to be related to the rotation instability. To explore the turbulence characteristics in the vaneless region, the Reynolds stress transportation equation is studied. In the vaneless region, the rotation term of the Reynolds stress transport equation is negligible compared to the production term, although the rotation instability is obvious near the diffuser. The production of the Reynolds stress plays the role of redistributing the energy from the uu component to the vv component, except for the region near the impeller outlet. Originality/value: The third-order SGS model DCNM has proved to be promising in simulating the rotor–stator interaction. The analysis of the rotation instability and the Reynolds stress transport equation shed light on the further understanding of the rotor–stator interaction.